Enhanced recovery after surgery (ERAS) versus standard recovery for gastric cancer patients: The evidences and the issues. (May 2022) - Rosa, Fausto; Longo, Fabio; Pozzo, Carmelo; Strippoli, Antonia; Quero, Giuseppe; Fiorillo, Claudio; Mele, Maria Cristina; Alfieri, Sergio
Abstract: The significant advances that have been reached, in the last decades, in the treatment of gastric cancer, contributed to the concept of enhanced recovery after surgery (ERAS) with the aim to reduce the surgical stress, accelerate postoperative recovery, and reduce the length of hospital stay. The most important items included in the ERAS protocols are the pre-operative patient education, early mobilization and immediate oral intake from the first postoperative day. The aim of this narrative review is to focus the attention on the possible advantages of ERAS program on perioperative functional recovery outcomes after gastrectomy for gastric cancer. Highlights: Surgery still represents the mainstay treatment for gastric cancer. Surgical treatment for gastric cancer is a high-risk procedure burdened with significant morbidity and mortality. The ERAS protocol has been successfully integrated into peri-operative management of different cancer surgeries. The ERAS protocol seems to be safe and effective also in the management of gastric cancer patients.